Implementing antibiotic stewardship in high-prescribing English general practices: a mixed-methods study - Tonkin-Crine, S; McLeod, M; Borek, A; Campbell, A; Anyanwu, P; Costelloe, C; Moore, M; Hayhoe, B; Pouwels, K; Roope, L; Morrell, L; Hopkins, S; et al. (Royal College of General Practitioners, 2023)
Background Trials have identified antimicrobial stewardship (AMS) strategies that effectively reduce antibiotic use in primary care. However, many are not commonly used in England. The authors co-developed an implementation intervention to improve use of three AMS strategies: enhanced communication strategies, delayed prescriptions, and point-of-care C-reactive protein tests (POC-CRPTs).